Education and knowledge: basic pillars of changing production patterns with social equity (UN. ECLAC SantiagoCL, 1992)
Outlines possible action with regard to policies and institutions which could further the systemic links between education, knowledge and development in the light of the conditions prevailing in the 1990s. Proposes a strategy which aims to create within the coming decade certain conditions with regard to education, training and the incorporation of scientific and technological progress which will make possible the transformation of the production patters of the region against a background of growing social equity.
DC